ISSUES OF DEVELOPMENT OF TEACHER-EDUCATOR'S SPEECH IN SCHOOL EDUCATIONAL ORGANIZATIONS - Imamova Nilufar Uktamovna; Khoshieva Gulmira Isrofil qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Mastering an exemplary speech for an educator is an indicator of his readiness for his profession. This article talks about the peculiarity of speech activity of a pedagogue in preschool education organizations.